Valorization of olive pruning biomass into high-efficiency activated carbon: CCD optimization and material characterization - Ismaeel Ahmed Nagim; Thouraya Bohli; Abdelmottaleb Ouederni (Center of Biomass & Renewable Energy (CBIORE), 2026)
This study focuses on the valorization of olive pruning stems (OPS) biomaterial into a high-efficiency adsorbent. The selected preparation method involved chemical activation using phosphoric acid (H₃PO₄) at a concentration of 50%. The effects of four process parameters: impregnation ratio, impregnation time, carbonization temperature and carbonization time, were studied using Central Composite Design (CCD) to optimize the iodine index, methylene blue index and phenol number of the produced AC. These indexes reflect the development of the AC porosity and its adsorption performances. Obtained results indicate that optimal activated carbon can be prepared under the following conditions: an impregnation ratio of 5.5 g/g, an impregnation time of 7 h, a carbonization temperature of 400°C, and a carbonization time of 1.5 h. Obtained activated carbon in these optimum conditions showed an iodine value of 947 mg/g, methylene blue index exceeding 267 mg/g and phenol number of approximately 35.637 mg/g. Based on the N₂ adsorption–desorption isotherm measurements, the optimized sample exhibited a BET surface area of 1604.8 m²/g, a total pore volume of 1.124 cm³/g, and an average pore size diameter of 20.8 nm. These results highlight the suitability of olive pruning rods as a high-quality precursor for producing effective activated carbon, which can be used for wastewater treatment and other applications.